Dog on trail with cabins in snow, Dawson, Yukon Territory, ca. 1901. - University of Washington Libraries. Special Collections Division
PH Coll 246.81 [Meed journal: "A winter landscape. Dawson Y.T. The solitary dog faces the photographer in the powdery dry fine snow."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number